Odpowiedzi

  • Użytkownik Zadane
2010-02-23T13:32:32+01:00
A) (x + 3)² = x² + 6x + 9

b) (3y + 2x)² = 9y² + 12xy + 4x²

c) (½x + 4y)² = ¼x² + 4xy + 16y²

d) (x - 5)² = x² - 10x + 25

e) (2x - 5)² = 4x² - 20x + 25

f) (x + 2)(x - 2) = x² - 4

g) (3y + 2x)(3y - 2x) = 9y² - 4x²

h) (2m - 10n)(2m + 10n) = 4m² - 100n²
Najlepsza Odpowiedź!
2010-02-23T14:54:36+01:00
A) (x+3)² = x²+6x+9

b) (3y+2x)² = 9y+12xy+4x²

c) (½x+4y)² = ¼x+4xy+16y²

d) (x-5)² = x²-10x+25

e) (2x-5)² = 4x²-20x+25

f) (x+2)(x-2) = x²-4

g) (3y+2x)(3y-2x) = 9y²-4x²

h) (2m-10n)(2m+10n) = 4m²-100n²